PENGARUH EXPERIENTIAL MARKETING, KUALITAS JASA, DAN KEPUASAN TERHADAP REPURCHASE INTENTION (Studi Kasus Pada Pengguna Bus Pariwisata PO Rimba Raya) - Jay Satriadi Danendra; Naili Farida (Jurnal Ilmu Administrasi Bisnis, 2018)
Otobus Company (PO) provides tour package service for travel. PO managers compete to increase the number of users by achieving repurchase intention, as many respondents argue that WiFi is often unrelated. It is also done by PO Rimba Raya (PT Rimba Raya Putra), but in 2014 to 2016 there was a decline in the number of tourist buses using fluctuations. This is because also in terms of facilities and services there are still complaints. This research aims to determine the effect between experiential marketing and service quality of PO Rimba Raya Tourism Bus to repurchase intention through satisfaction as an intervening variable. The type of research is explanatory research, with a sample of 100 respondents who use PO Rimba Raya through purposive sampling technique. The method of analysis used in this research was two steps regressions analysis. The results showed that there was influence between experiential marketing and quality significantly to satisfaction, and satisfaction had an effect on repurchase intention. Based on the results of two-stage regression analysis, it is known that the influence of service quality is greater than experiential marketing on satisfaction, then the satisfaction variable has an effect on repurchase intention variable. Furthermore, the satisfaction variable acts as a mediation variable indicating the indirect influence between experiential marketing and service quality on repurchase intention. The advice for PO Rimba Raya is to update the fleet periodically, improve the quality of service and facilities, the condition of the bus fleet on the way to be safe.